2012
DOI: 10.4171/jncg/98
|View full text |Cite
|
Sign up to set email alerts
|

A categorical approach to cyclic duality

Abstract: Abstract. The aim of this paper is to provide a unifying categorical framework for the many examples of para-(co)cyclic modules arising from Hopf cyclic theory. Functoriality of the coefficients is immediate in this approach. A functor corresponding to Connes's cyclic duality is constructed. Our methods allow, in particular, to extend Hopf cyclic theory to (Hopf) bialgebroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…for m P M . As mentioned in [BöS ¸t1,§A.7] and similarly as for comodules, a right Ucontramodule additionally induces a left A-action given by…”
Section: Contramodules Over Bialgebroidsmentioning
confidence: 95%
“…for m P M . As mentioned in [BöS ¸t1,§A.7] and similarly as for comodules, a right Ucontramodule additionally induces a left A-action given by…”
Section: Contramodules Over Bialgebroidsmentioning
confidence: 95%
“…Using the adjunctions for M, V, W ∈ H M: We want to understand the center Z H M ( H M op ). First of all let us recall the notion of contramodules over bialgebroids (as it was defined in [2], generalizing the classical contramodules for coalgebras [8]).…”
Section: Anti-yetter-drinfeld Contramodules For Hopf Algebroidsmentioning
confidence: 99%
“…This object is precisely the one constructed in [3] as recalled in Section 2.4 above. This construction was generalized slightly in [5] to include right λ-coalgebra structures on arbitrary functors Y → X, rather than just objects of X; in this case y becomes a functor Y → H 0 (A, X) and the composite…”
Section: 4mentioning
confidence: 99%
“…Just as simplicial structure can be used to define homology, cyclic (or duplicial or paracyclic) structure can be used to define cyclic homology. In a series of papers [3,4,5], Böhm and Ştefan looked at what further structure than a comonad is needed to equip the induced simplicial object with duplicial structure; the main extra ingredient turned out to be a second comonad with a distributive law [2] between the two. They also showed that their machinery could be used to construct the cyclic homology of bialgebroids.…”
Section: Introductionmentioning
confidence: 99%